Problem Pluralisme Agama di Indonesia - M. Adib Fuadi Nuriz; Achmad Reza Hutama Al Faruqi; Martin Putra Perdana (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2021)
Abstract This article examines the problem of religious pluralism that has always been echoed by liberals, so that the thinking of Muslims is often disturbed. This religious pluralism which often under the guise of tolerance easily poison the minds Muslims, especially ordinary people with their thoughts. In this article, the author examines the ideas of Prof. Harun Nasution, because he is one of the most famous figures in Indonesia with his work "Islam Ditinjau dari Berbagai Aspeknya ". The result is that precautions need to be taken so that this kind of thinking does not further damage future generations of Islam. The commitment to continue to uphold Islam as the truest religious identity (truth claim) needs to be instilled. As well as the introduction and deepening of the basics of Islamic values, tauhid, syari'at and the view that religious pluralism is a wrong view in understanding religions so it should be avoided.